A necessidade de regulamentação do teletrabalho como meio de efetivação dos direitos fundamentais dos trabalhadores - Nascimento, Carlota Bertoli (2012)
Telework is the living example of the mutations of human relations, which are present in different ways from those observed during the industrial era. In postindustrialism is not possible to observe labor relations under the magnifying glass of the paradigms juslaborais built during the solid modernity, failing to derail the enjoyment of fundamental rights for teleworkers, as the new way of working ignores the geographical and temporal boundaries determinants so far in working relationships, enabling a revolution in existing capital-labor relations. This work faces the problem of the antiquity of the existing labor legislation that fails to give effect to fundamental rights earned over the years by workers because the base resistance under which it was forged, not allowing your application via interpretative without that violates the systematic legal Constitutional adopted. The legislative model liberal industrial not providing legal certainty for workers and employers by making an appropriate regulation of new forms of work in order that they can accomplish fundamental rights. For that we use as a paradigm of comparative labor law that Portugal has evolved and is weighted in relation to the conceptualization and limitation of telework, providing the desired social and legal security that is sought with the enactment of law.